Annual bacterial community cycle in a seasonally ice‐covered river reflects environmental and climatic conditions. (13th February 2019) - Cruaud, Perrine; Vigneron, Adrien; Fradette, Marie‐Stéphanie; Dorea, Caetano C.; Culley, Alexander I.; Rodriguez, Manuel J.; Charette, Steve J.
Abstract: Bacteria are key players in biogeochemical cycles and control water quality in freshwater ecosystems. Nevertheless, little is known about the identity and ecology of riverine bacteria, especially during ice‐covered periods that are often mistakenly perceived as periods with negligible biological activities. Here, we analyzed in detail the effects of environmental and climatic conditions on freshwater bacterial community structure and diversity over a 2‐yr sampling campaign, targeting a seasonally ice‐covered river of the Quebec City (Canada) area, the Saint‐Charles River. Quantitative polymerase chain reaction and 16S ribosomal RNA gene high‐throughput sequencing demonstrated a strong seasonal cycle of the bacterial community composition with rapid successions of bacterial lineages, reflecting the harsh climatic condition of the region. During the summer, the bacterial community was dominated by typical freshwater microorganisms such as Limnohabitans, Sporichthyaceae hgcI/acI clade, and Pseudarcicella . In contrast, the results suggest that during the cold season, the low water temperatures, combined with other prevailing conditions such as reduced light availability and minimal particulate inputs from the catchment, created various environmental niches for potential methanotrophic Gammaproteobacteria, such as Crenothrix and Methylobacter, other Betaproteobacteria, such as Candidatus Methylopumilus, Candidatus Nitrotoga, and Rhodoferax, as well as Verrucomicrobia and Parcubacteria . The presence of these taxa in the winter suggests active carbon, iron, and nitrogen cycling under ice, whereas summer lineages are dormant or in a phase of reduced activity. These results increase our understanding of bacterial dynamic and potential metabolic processes occurring in seasonally ice‐covered inland waters, providing evidence that winter can be an especially important period for freshwater ecological processes.